OPTIMIZATION OF OPERATING CONDITIONS FOR GAS AND GAS CONDENSATE WELLS AT THE FINAL STAGE OF DEVELOPMENT - Matkivskyі S. V.; Matiishyn, L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
A special period in the development of oil and gas fields is the final stage, which is usually accompanied by various complications and significant capital investments and requires the introduction of new technologies and methods of production. The complexity of residual hydrocarbon reserves is associated with low reservoir pressures, accumulation of fluid at the bottom of wells, the formation of sand plugs, breaks in tubing, corrosion of surface and underground equipment. In this regard, the existing well stock is operated periodically, which negatively affects the performance of hydrocarbon production. This article analyzes the main methods of intensifying the operation of gas and gas condensate wells, which are used in the gas industry to remove liquid from the bottom of wells and allow hydrocarbon production with minimal losses. Using Schlumberger’s PipeSim software, a nodal analysis was performed for a specific production well. Based on the results of the studies, it was found that the operation of the well is unstable with a constant accumulation of fluid at the bottomhole. To optimize the operating conditions of a borehole, a study was made of the effectiveness of deepening the tubing string. According to the results of the calculations, taking into account the clearance of the tubing to the middle of the perforation interval, it was established that the liquid is removed. Liquid loading velocity ratio LLVR<1, gas velocity increases from 1.030 m/s for the base case to 6.896 m/s for the case with tubing deepening. In this case, Liquid loading velocity ratio decreases from 1.984 to 0.303, respectively. Thus, by increasing the depth of the descent of the tubing string, the removal of all liquid from the bottomhole is ensured and stable operation of the production well is achieved over a long period of field development. The practical implementation of optimization systems for the development of gas and gas condensate fields in the broadest sense of the problem will significantly intensify the process of gas and condensate production and reach the level of solving the problem.